2011 IEEE SENSORS Proceedings 2011
DOI: 10.1109/icsens.2011.6127262
|View full text |Cite
|
Sign up to set email alerts
|

On-body to on-body channel characterization

Abstract: Interest in on-body communication channels is growing as the use of wireless devices increases in medical, consumer and military sensor applications. This paper presents an experimental investigation and analysis of the narrowband on-body propagation channel. This analysis considers each of the factors affecting the channel during a range of stationary and motion activities in different environments with actual wireless mote devices on the body. Use of such motes allows greater freedom in the subject's movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…On the other hand, on-body links are governed by creeping waves, which are diffracted by human tissues and spread out along the human body [10]. Previous measurements [9] indicate that creeping waves are rarely disturbed by multi-path fading (small-scale fading) or large-scale fading caused by Tx-Rx distance changes or shadowing, but are largely influenced by body motions. Thus, we see that distinct propagation patterns exist between on-and off-body signals.…”
Section: Exploiting Distinct Radio Propagation Patterns Between Omentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, on-body links are governed by creeping waves, which are diffracted by human tissues and spread out along the human body [10]. Previous measurements [9] indicate that creeping waves are rarely disturbed by multi-path fading (small-scale fading) or large-scale fading caused by Tx-Rx distance changes or shadowing, but are largely influenced by body motions. Thus, we see that distinct propagation patterns exist between on-and off-body signals.…”
Section: Exploiting Distinct Radio Propagation Patterns Between Omentioning
confidence: 99%
“…The salient physical layer (PHY) signatures underlying different BANs present us with an exciting opportunity. In BAN channels, off-body signals are mainly comprised of line-of-sight (LOS) and multi-path components, while onbody signals are governed by creeping waves [9], [10]. The distinct radio propagation patterns potentially enable a general security solution relying on prevalent wireless chips.…”
Section: Introductionmentioning
confidence: 99%
“…Received signals of on-body sensors are further affected by human movements and motions, device placement, and surrounding environment. As shown in [51], for on-body channels, the distance between transmitter and receiver is weakly correlated to the path loss since shadowing effect is more influential due to different body shapes. Besides, [52] stated that shadowing can be also caused by voluntary and involuntary movements, which affects LOS.…”
Section: B Theoretical Explanationmentioning
confidence: 99%
“…For different positions on the body, the received signals are further affected by human movements, device placement and surrounding environment. [9] has shown that for on-body channels, the distance between transmitter and receiver has weak correlation to the path loss since shadowing effect has more influence due to different body shapes. Besides, [8] points out that both voluntary and involuntary movements also cause shadowing affecting the line-of-sight.…”
Section: Theoretical Explanationmentioning
confidence: 99%